Metallic coplanar resonators optimized for low-temperature measurements. (8th September 2016) - Javaheri Rahim, Mojtaba; Lehleiter, Thomas; Bothner, Daniel; Krellner, Cornelius; Koelle, Dieter; Kleiner, Reinhold; Dressel, Martin; Scheffler, Marc
Abstract: Metallic coplanar microwave resonators are widely employed at room temperature, but their low-temperature performance has received little attention so far. We characterize compact copper coplanar resonators with multiple modes from 2.5 to 20 GHz at temperatures as low as 5 K. We investigate the influence of center conductor width (20–100 µ m) and coupling gap size (10–50 µ m), and we observe a strong increase of quality factor ( Q ) for wider center conductors, reaching values up to 470. The magnetic-field dependence of the resonators is weak, with a maximum change in Q of 3.5% for an applied field of 7 T. This makes these metallic resonators well suitable for magnetic resonance studies, as we document with electron spin resonance (ESR) measurements at multiple resonance frequencies.